Pattern and Amount of Smartphone Usage Among Older Adults Living in Nonthaburi Province - Supapong, Jantiga; Ngamsnit , Soraya (Journal of Humanities and Social Sciences, Rajapruk University, 2026)
The objectives of this research were to study the patterns, amount, and contextual factors associated with smartphone usage among older adults in Nonthaburi Province. This study employed a Mixed Methods Research design, combining a survey and qualitative research. Data were collected from a sample of 400 older adults, followed by purposive sampling of 30 key informants. The research instruments included a questionnaire with an Index of Item-Objective Congruence (IOC) between 0.67 and 1.00 and an in-depth interview guide. Data were analyzed using descriptive statistics and content analysis based on pre-defined key themes. The results revealed that smartphone usage patterns among older adults can be categorized into two primary groups: 1) The Smartphone-Control Group, characterized by proactive usage to fulfill instrumental needs for managing daily routines and transactions; and 2) The Smartphone-Dependent Group, characterized by reactive usage to fulfill affective needs, such as alleviating loneliness and building social connectivity. Regarding the contextual factors associated with usage patterns and amount, digital self-efficacy and living contexts—particularly living alone or lack of caregivers—acted as catalysts for self-reliance through smartphones. Additionally, older adults with high usage necessity employed compensatory adaptation mechanisms, such as font size adjustments and device settings, to maintain Active Ageing and social participation.